#### Answer

$y' = \frac{-12}{p^4}$

#### Work Step by Step

$y = \frac{4}{p^3} = 4p^{-3}$
Power rule: $y' = 4(-3)p^{(-3-1)} = \frac{-12}{p^4}$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$y' = \frac{-12}{p^4}$

$y = \frac{4}{p^3} = 4p^{-3}$
Power rule: $y' = 4(-3)p^{(-3-1)} = \frac{-12}{p^4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.